Chelation Behaviour of Aceturic Acid with Co(II), Ni(II) and Cu(II) - Kumar, Umesh; Singh, Puja; Sharma, Shivadhar (Asian Journal of Chemistry, 2015)
Aceturic acid consists of two parts e.g., peptide part i.e., CH3CONH and -COOH part. It may act as bidentate ligand coordinating through either peptide or carboxylic acid part or both peptide as well as carboxylic acid part simultaneously forming chelates with transition metal ions. Some complexes of Co(II), Ni(II) and Cu(II) with aceturic acid have been prepared. The microanalysis and electrical conductivity of complexes revealed the formulation of complexes as ML2X2 where 'L' is aceturic acid and X' stands for a-picoline or pyridine. The comparison of infrared spectra of complexes with that of free ligand confirms the ligation point of the ligand through carboxylic acid and nitrogen of peptide part. Thus a 5-membered chelates are formed with Co(II), Ni(II) and Cu(II). The magnetic moment values of Co(II) complexes were found in the range of 4.90-4.93 BM at room temperature while it was in the range of 3.32-3.39 BM for Ni(II) complexes. Cu(II) complexes recorded magnetic moment 1.98-2.10 BM. These values are informative of octahedral symmetry around the metal ion which was confirmed by the electronic spectra of complexes.